Multi-Detailed 3D Architectural Framework for Sound Perception Research in Virtual Reality - Llorca-Bofí, Josep; Vorländer, Michael (Frontiers in Built Environment, 2021)
Presentation of architectural design in simulation environments demands strong 3D modeling abilities. Architects usually demonstrate presentation skills that mostly address researchers in the building simulation field. However, there is still a gap between the architect’s deliverable and the contextual scenario for overarching research purposes, mainly caused by the lack of knowledge in the areas where research disciplines overlap. This dilemma is particularly present in the practice of 3D modeling for soundscape research in Virtual Reality, since the building modelers must gather also diverse pieces of knowledge into a contained scenario: ranging from sound sources, sound propagation models to physically-based material models. Grounded on this need, this paper presents a comprehensive framework, defined by the visual and acoustic cues - geometries, materials, sources, receivers, and post-processing - on one side, and three levels of detail, on the other. In this way, very specific research application needs can be covered, as well as a modular concept for future modeling demands. The interconnection between every model element is particularly designed, enabling the assembly among different modalities at different levels of detail. Finally, it provides targeted modeling strategies for architects, depicted in one indoor and one outdoor demonstrators for auditory-visual research.